Macrozoobenthos Community Structure in Mangrove Forest at Purnama Urban Village, Dumai City - Sihotang, Yula Elawati; Nasution, Syafruddin; Elizal, Elizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The structure of the macrozoobenthos community in the mangrove forest area of Purnama Village, Dumai City can be used as a basis for knowing the environmental conditions of the waters in the mangrove forest of Purnama Village, Dumai City. This research was conducted in the mangrove forest area of Purnama Village, Dumai City in April 2018. The method used was the survey method, sampling was done by purposive sampling. The research location was divided into three stations and each station was divided into three transects, with each transect placed three 1 m2plots. The results showed an abundance of macrozoobenthos ranging from 7.56-10.00 Ind / m2, obtained 3 classes namely Gastropoda, Crustacea, and Bivalva consisting of 12 species namely Cassidula aurisfelis, Cerithidea obtuse, Littorina melanostoma, Nerita lineata, Nerita violacea, Littorina scabra , Chicoreus capucinus, Indothais gradate, Nassarius candens, Uca sp, Polymesoda expansa, Indothais malayensis and the most commonly found are Nerita lineata while the diversity index ranges from 2.79 to 2.98, the uniformity index ranges from 1.09 to 1.33, index dominance ranged from 0.15 to 1.16 and distribution patterns ranged from 2.53 to 3.32. The results of measurement of environmental parameters are still within the optimal limits for the life of marine biota and the dominant type of sediment is muddy. It was concluded that moderate species diversity, balanced uniformity and no dominant species were found while the distribution pattern was grouped. Keywords: Community Structure, Macrozoobenthos, Mangrove, Dumai City